Efektivitas Layanan Bimbingan Klasikal Teknik Permainan Simulasi Untuk Mereduksi Kejenuhan Belajar Pada Siswa - Anandica, Novaresta; I Wayan Dharmayana; Adif Jawadi Saputra (UNIVERSITAS BENGKULU, 2025)
Abstract This study aims to determine the effectiveness of classical guidance services using simulation game techniques in reducing students' learning burnout. The research employed a quantitative experimental method with a two-group pretest-posttest control design. The subjects consisted of 50 students from SMK N 4 Kota Bengkulu, who were divided into two groups: an experimental group and a control group, each consisting of 25 students selected through simple random sampling. Data were analyzed using an independent samples t-test. The results showed a t-value of 36.70 with a significance value (2-tailed) of .000 (p<0.05), indicating a significant difference in learning burnout levels between the experimental and control groups. These findings suggest that classical guidance services using simulation game techniques are effective in reducing students' learning burnout. Keywords: learning burnout, classical guidance services, simulation games